Pemahaman Peraturan, Plagiasi di Perguruan Tinggi, dan Implikasi Etis Penggunaan AI dalam Penyelesaian Skripsi - Harida, Ratri; Arifin, Muh. Zainul; Novitasari, Lusy (Universitas Muhammadiyah Magelang, 2026)
This study aims to identify the understanding of S-1 education students towards the Regulation of the Minister of National Education No. 17 of 2010 concerning the Prevention and Prevention of Plagiarism and their perception of the ethical implications of the use of artificial intelligence (AI) in thesis completion. The method used was quantitative descriptive with a purposive sampling technique for 40 final semester students at the Ponorogo private LPTK who were or had just completed their thesis. Data collection was carried out through an online questionnaire that included demographic data, understanding of plagiarism regulations, and perceptions of the use of AI. Data analysis was carried out descriptively through frequency distribution and score categorization. The results show that 97.5% of students have used AI with varying levels of frequency, driven by the need for time efficiency, especially for 60% of respondents who work while studying. Students have a fairly good understanding of conventional plagiarism and recognize the benefits of AI, but lack concrete ethical guidance due to regulatory ambiguities that have not explicitly regulated AI. This study concludes that it is necessary to update regulations, develop an AI literacy curriculum, strengthen the role of supervisors, and an educational approach that guides students to become critical and responsible AI users in order to maintain academic integrity in the era of artificial intelligence.